2000
DOI: 10.1053/jhep.2000.20349
|View full text |Cite
|
Sign up to set email alerts
|

Flow-cytometric separation and enrichment of hepatic progenitor cells in the developing mouse liver

Abstract: Stem cells responsible for tissue maintenance and repair are found in a number of organs. However, hepatic stem cells assumed to play a key role in liver development and regeneration remain to be well characterized. To address this issue, we set up a culture system in which primitive hepatic progenitor cells formed colonies. By combining this culture system with fluorescence-activated cell sorting (FACS), cells forming colonies containing distinct hepatocytes and cholangiocytes were identified in the fetal mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
250
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(263 citation statements)
references
References 41 publications
(51 reference statements)
11
250
0
1
Order By: Relevance
“…20 However, unlike oval cells, they do not express hepatocyte or cholangiocyte specific markers and c-kit. 21 Cells derived from a single H-CFU-C expand in vitro and are capable of reconstituting hepatocytic, bile-ductal, pancreatic and intestinal structures in vivo . 20 Whether H-CFU-C's exist in the adult liver has not been established; however, these cells may represent the resident hepatocyte progenitor.…”
Section: Oval Cell Originmentioning
confidence: 99%
“…20 However, unlike oval cells, they do not express hepatocyte or cholangiocyte specific markers and c-kit. 21 Cells derived from a single H-CFU-C expand in vitro and are capable of reconstituting hepatocytic, bile-ductal, pancreatic and intestinal structures in vivo . 20 Whether H-CFU-C's exist in the adult liver has not been established; however, these cells may represent the resident hepatocyte progenitor.…”
Section: Oval Cell Originmentioning
confidence: 99%
“…These signaling mechanisms may occur between stem cells, between support cells and stem cells, and between stem cells and differentiating cells. Cell/cell and cell/ECM adhesion and signaling in adult niches is mediated through cell adhesion receptors such as cadherins (Song et al, 2002;Zhang et al, 2003) and integrins (Jones and Watt, 1993;Shinohara et al, 1999;Suzuki et al, 2000;Fujimoto et al, 2002;Frye et al, 2003;Scott et al, 2003;Blanpain et al, 2004;Chen et al, 2004;Deb et al, 2004;Hidalgo et al, 2004;Corbel et al, 2005;Priestley et al, 2005;Wagers and Weissman, 2005;Bajanca et al, 2006;Pajoohesh-Ganji et al, 2006;Lawson et al, 2007;Yang et al, 2007). In this model, as a cell moves away from the niche and thus away from some regulatory signals, it adopts a differentiated phenotype as shown in the pair of cells to the right.…”
Section: Introductionmentioning
confidence: 99%
“…After evaluating a large panel of markers because no single antigen had been definitely validated (30), we observed that all of the cultured cells expressed the a6 and b1 integrins, fundamental in ensuring cell adhesion and clonality of hepatic progenitor cells (1,2). EpCAM and CD133 antigens were also expressed on freshly isolated L-EpPCs, but their reactivity progressively decreased as the cells matured, as also suggested by the gradual increase in CD166 and a1-antitrypsin positivity during culture.…”
Section: Discussionmentioning
confidence: 92%
“…Media were changed three times a week. LEnPCs and L-EpPCs were counted at each passage and, at the first and fifth passages, characterized for the expression of various markers (1,2,16,17,(19)(20)(21).…”
Section: In Vitro Cell Culturesmentioning
confidence: 99%